Some Reliefs Representing the King in the Heb Sed Robe Discovered in the Henket-Ankh - Chapon, Linda (Études et Travaux, 2018)
During the archaeological fieldwork undertaken in the Henket-Ankh, the Temple of Millions of Years of Thutmose III situated between el-Assasif and el-Khokha, a large amount of sandstone blocks and fragments have been discovered. Although they are quite fragmented, they enable us to posit a hypothesis about some of the scenes that were originally carved on the temple’s walls. This paper focuses mainly on the fragments representing the king in the Heb Sed robe. The Heb Sed robe embodies royal power regeneration. It is therefore especially significant in the Temples of Millions of Years where this aspect played a key role. These reliefs would contribute to the already known iconographic corpus of this period, as well as to the understanding of the temple iconographic programme and function.